Radiation Therapy Techniques and Treatment-Related Toxicity in the PORTEC-3 Trial: Comparison of 3-Dimensional Conformal Radiation Therapy Versus Intensity-Modulated Radiation Therapy - Wortman, Bastiaan G.; Post, Cathalijne C.B.; Powell, Melanie E.; Khaw, Pearly; Fyles, Anthony; D'Amico, Romerai; Haie-Meder, Christine; Jürgenliemk-Schulz, Ina M.; McCormack, Mary; Do, Viet; Katsaros, Dionyssios; Bessette, Paul; et al. (International journal of radiation oncology, biology, physics, 2022)
Radiation therapy techniques have developed from 3-dimensional conformal radiation therapy (3DCRT) to intensity modulated radiation therapy (IMRT), with better sparing of the surrounding normal tissues. The current analysis aimed to investigate whether IMRT, compared to 3DCRT, resulted in fewer adverse events (AEs) and patient-reported symptoms in the randomized PORTEC-3 trial for high-risk endometrial cancer. Data on AEs and patient-reported quality of life (QoL) of the PORTEC-3 trial were available for analysis. Physician-reported AEs were graded using Common Terminology Criteria for Adverse Events v3.0. QoL was assessed by the European Organisation for Research and Treatment of Cancer QLQC30, CX24, and OV28 questionnaires. Data were compared between 3DCRT and IMRT. A P value of ≤ .01 was considered statistically significant due to the risk of multiple testing. For QoL, combined scores 1 to 2 (“not at all” and “a little”) versus 3 to 4 (“quite a bit” and “very much”) were compared between the techniques. Of 658 evaluable patients, 559 received 3DCRT and 99 IMRT. Median follow-up was 74.6 months. During treatment no significant differences were observed, with a trend for more grade ≥3 AEs, mostly hematologic and gastrointestinal, after 3DCRT (37.7% vs 26.3%, P = .03). During follow-up, 15.4% (vs 4%) had grade ≥2 diarrhea, and 26.1% (vs 13.1%) had grade ≥2 hematologic AEs after 3DCRT (vs IMRT) (both P < .01). Among 574 (87%) patients evaluable for QoL, 494 received 3DCRT and 80 IMRT. During treatment, 37.5% (vs 28.6%) reported diarrhea after 3DCRT (vs IMRT) (P = .125); 22.1% (versus 10.0%) bowel urgency (P = 0039), and 18.2% and 8.6% abdominal cramps (P = .058). Other QoL scores showed no differences. IMRT resulted in fewer grade ≥3 AEs during treatment and significantly lower rates of grade ≥2 diarrhea and hematologic AEs during follow-up. Trends toward fewer patient-reported bowel urgency and abdominal cramps were observed after IMRT compared to 3DCRT.